2020
DOI: 10.1186/s13054-020-03375-7
|View full text |Cite
|
Sign up to set email alerts
|

Dosing of thromboprophylaxis and mortality in critically ill COVID-19 patients

Abstract: Background A substantial proportion of critically ill COVID-19 patients develop thromboembolic complications, but it is unclear whether higher doses of thromboprophylaxis are associated with lower mortality rates. The purpose of the study was to evaluate the association between initial dosing strategy of thromboprophylaxis in critically ill COVID-19 patients and the risk of death, thromboembolism, and bleeding. Method In this retrospective study, all critically ill COVID-19 patients admitted to two intensive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 31 publications
3
70
1
1
Order By: Relevance
“…Importantly, there was no difference in the development of bleeding events among the three groups. 27 Similar findings were identified in a retrospective study from Abu Dhabi albeit finding that therapeutic anticoagulation, rather than enhanced chemoprophylaxis, was associated with major bleeding. 28 Another retrospective observational study of 468 hospitalized patients in the United States found that initial use of enhanced dosing thromboprophylaxis correlated with a downtrend in D -dimer levels and was associated with improved 30-day mortality without a significant increased rate of bleeding.…”
Section: Questionssupporting
confidence: 76%
“…Importantly, there was no difference in the development of bleeding events among the three groups. 27 Similar findings were identified in a retrospective study from Abu Dhabi albeit finding that therapeutic anticoagulation, rather than enhanced chemoprophylaxis, was associated with major bleeding. 28 Another retrospective observational study of 468 hospitalized patients in the United States found that initial use of enhanced dosing thromboprophylaxis correlated with a downtrend in D -dimer levels and was associated with improved 30-day mortality without a significant increased rate of bleeding.…”
Section: Questionssupporting
confidence: 76%
“…A retrospective study comparing patients with COVID-19 to those with Influenza A evaluated the effects of different thromboprophylaxis strategies on 152 patients admitted to 2 intensive care units. An association between high dose (200 UI x kg per day) dalteparin and reduction of mortality in respect to those receiving low or middle dose of heparin was reported (hazard ratio of death 0.33; 95% confidence intervals 0.13–0.87) [ 69 , 70 ]. Although the majority of the studies report a favorable effect of anticoagulant therapy, no consensus exists about the timing and dosage of heparins in patients with COVID-19 [ 71 ].…”
Section: Management Of Viral Pneumoniamentioning
confidence: 99%
“…Despite the data on the effectiveness of heparin drugs in reducing mortality in severe COVID-19 patients, and despite thromboprophylaxis [ 7 , 8 ], the development of venous and arterial thromboembolic complications has been reported. There is also a problem with the optimal dosage of anticoagulant agent [ 5 , 9 , 10 , 11 ]. Thus, there are a number of unresolved issues regarding the use of these drugs.…”
Section: Introductionmentioning
confidence: 99%